PKM KELOMPOK GURU SMK KARYA GUNA DI KEC. TEBET JAKARTA SELATAN DALAM MEMBUAT WEBLOG MENGGUNAKAN BLOGSPOT SEBAGAI MEDIA PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Endaryono; Aswin Saputra; Mahyudi (Bajang Institute, 2021)
Abstract: The social restriction policy has an impact on various fields including the field of formal education. Learning which is usually done face-to-face between teachers and students in government classrooms applies learning methods with an online system or in a network (online). Online learning or online learning is learning without face to face directly but is done online through the internet network. The same thing happened in Guna's SMK, Jalan Manggarai Utara No. 01 Ex. Manggarai district. Tebet, South Jakarta. In teaching and learning activities are carried out online or online. Online learning requires several media applications that are effective, easily accessible, and understood by teachers and students. These applications include: whatsapp, telegram, instagram, zoom application, googlemeet or other media as learning media. As an alternative media for learning media, our community service team proposes blog media as an online learning medium. The team offers weblog creation training activities using blogspot as an online learning medium